Aromatase inhibitors with or without gonadotropin-releasing hormone analogue in metastatic male breast cancer: A case series - Zagouri, F.; Sergentanis, T.N.; Koutoulidis, V.; Sparber, C.; Steger, G.G.; Dubsky, P.; Zografos, G.C.; Psaltopoulou, T.; Gnant, M.; Dimopoulos, M.-A.; Bartsch, R. (British Journal of Cancer, 2013)
Background:Data regarding the safety and effectiveness of aromatase inhibitors (AIs) as monotherapy or combined with gonadotropin-releasing hormone (GnRH) analogue in male breast cancer are scarce. Methods: In this retrospective chart review, cases of male breast cancer patients treated with AIs with or without a GnRH analogue were evaluated. Results: Twenty-three men were included into this case series. Aromatase inhibitors in combination with or without a GnRH analogue were given as first-line therapy in 60.9% and as second-line therapy in 39.1% of patients, respectively. All patients had visceral metastases, whereas in five of them bone lesions coexisted. In all cases AIs were tolerated well, and no case of grade 3 and 4 adverse events was reported. A partial response was observed in 26.1% of patients and stable disease in 56.5%. Median overall survival (OS) was 39 months and median progression-free survival (PFS) was 13 months. Regarding OS and PFS, no significant effects of GnRH analogue co-administration or type of AI were noted.Conclusion:Our study shows that AIs with or without GnRH analogues may represent an effective and safe treatment option for hormone-receptor positive, pretreated, metastatic, male breast cancer patients. © 2013 Cancer Research UK. All rights reserved.
Keywords: Anastrazole; Aromatase inhibitors; Exemestane; Letrozole; Male breast cancer